The Dialectics of Metacognition and Spirituality: Integrating Self-Regulated Learning within the Islamic Intellectual Tradition - Ahmad Muzakkil Anam; Alparslan Acikgenc; Moh Irsyad Fahmi MR; Noor Alwiyah (Dialogium: Journal of Islamic Studies, 2026)
In the 21st-century educational landscape, the focus has shifted from content acquisition to the mastery of "how to learn," placing Self-Regulated Learning (SRL) as a pivotal competency. However, modern SRL often lacks a spiritual dimension, appearing mechanistic in its approach. This study aims to explore the integration of SRL with Islamic values to create a more holistic and transcendental learning model. Using a qualitative-descriptive method with a literature review approach, this study synthesizes modern cognitive theories with classical Islamic intellectual traditions, specifically the concepts of muhasabah (self-reflection) and muraqabah (mindfulness of God). The findings reveal that integrating Islamic values into SRL transforms learning from a secular necessity into a form of "intellectual worship" (thalabul ilmi). The phase of forethought is strengthened by niyyah (intentionality), performance is guided by istiqamah (consistency) and muraqabah, and self-reflection is manifested through honest muhasabah. This synergy creates a "theocentric metacognition" that fosters not only academic excellence but also moral integrity. The study concludes that revitalizing Islamic education through an integrated SRL framework is essential for developing lifelong learners who possess both intellectual sovereignty and spiritual wisdom, enabling them to navigate the disruptions of the digital era with a grounded religious identity.